Organic dye-sensitized photovoltaic fibers. (1st July 2017) - Peng, Ming; Dong, Bin; Cai, Xin; Wang, Wei; Jiang, Xiaoming; Wang, Yuhong; Yang, Yong; Zou, Dechun
Graphical abstract: Highlights: Organic dyes are applied to photovoltaic fibers and modules for the first time. Organic dye-sensitized photovoltaic fibers achieved efficiency of >3%. Waveguide photovoltaic fibers achieve power output enhancement up to 2.7. Abstract: This work reports photovoltaic fibers based on organic dyes and their waveguide photovoltaic modules. The organic photovoltaic fibers achieve energy conversion efficiency of > 3% via balancing dye adsorption and interface charge recombination. The waveguide modules achieve power output enhancement up to 2.7. Suitable partners of organic dyes and luminescent solar concentrators would break through conventional thinking of extending absorption region of organic dyes to improve photovoltaic performance and would contribute to high power output with narrow-absorption sensitizers. As far as we know, this is the first time that organic dyes are involved in fiber solar cells and their modules. Our study may open a door toward cost-effective, lightweight and efficient building integrated photovoltaic power sources.